MAKNA PERUBAHAN ORGANISASIONAL INSTITUSI PENDIDIKAN TINGGI TENAGA KESEHATAN DALAM PERSPEKTIF MANAJEMEN (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2015)
This study was intended to get description and explanation about organizational change happening in the institution of higher education of health personnel of the health polytechnic. The research approach used was qualitative research with the phenomenon analysis at the Health Polytechnic of Surabaya based on management perspective. The results of the study were as follows: (1) to enable the institution be able to follow the development of the globalization era and the progress in education so that   the management of educational institutions were becoming increasingly clear and well focused in terms of the development of the organization, the management of educational program, the career path development of teaching staff in the future, (2) the performance achievement of efficiency in organizing the institution, (3) organization resources were becoming large, big, and complete to fulfill the need. (4) authority and creativity were limited, (5) less of autonomy of the academy after being just study programs, (6) loss of certain existed positions previously in the organization